Recent advances in understanding the flow over bluff bodies with different geometries at moderate Reynolds numbers - Lekkala, Malakonda Reddy (author); Latheef, Mohamed (author); Jung, Jae Hwan (author); Coraddu, A. (author); Zhu, Hongjun (author); Srinil, Narakorn (author); Lee, Byung Hyuk (author); Kim, Do Kyun (author) (Ocean Engineering, 2022)
The application of unsteady incompressible flow phenomenon over the bluff bodies has received the attention of many researchers due to the rich and complex physics underpinning these flows, and thus requiring special attention in their modelling and numerical simulations. The wake that forms at the leeside of the bluff body is of particular interest. Reynolds number and geometry are in turn two prominent parameters that govern the formation and subsequent behaviour of this wake. This paper reviews the wake formations for different cylindrical bluff bodies cross-sections such as circular, elliptical, helically twisted elliptical, symmetric wavy, asymmetric wavy, and harbor seal vibrissae cylinders. Alongside the Reynolds number and geometrical shape, the impacts of rotational rate, aspect ratio, angle of attack, and gap ratio between the cylinder and the bottom wall on the hydrodynamic coefficients, Strouhal number, recirculation length and suppression of vortex shedding in the cylinder wake are investigated. In addition, the variation of hydrodynamic coefficients for different cylindrical shapes are compared. Finally, concluding remarks are drawn based on recent advances in understanding the flow features and predictions with CFD methods. Ship Design, Production and Operations